EFIKASI DOSEN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PADA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS ISLAM KH. RUHIAT CIPASUNG TASIKMALAYA - Lelah Nurjamilah; Hanafiah Hanafiah; Faiz Karim Fatkhullah (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
Faculty efficacy is one of the key factors influencing the quality of learning in higher education, particularly in the Islamic Religious Education (IRE) program, which requires the integration of academic and pedagogical competencies with Islamic values. This study aims to analyze faculty efficacy in improving the quality of learning in the Islamic Religious Education program at KH. Ruhiat Cipasung Islamic University in Tasikmalaya. The study employed a qualitative approach using a descriptive method. Data were collected through in-depth interviews, observations, and document analysis involving 5 tenured faculty members, 1 Program Chair, and 10 students. Data analysis was conducted using the interactive model by Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that lecturers possess a high level of efficacy in mastering course content, applying teaching strategies, managing the classroom, conducting assessments, and utilizing instructional media. Lecturers’ efficacy is supported by teaching experience as well as institutional support through training and academic supervision. The research findings indicate that lecturers’ efficacy contributes to the creation of learning that is more effective, participatory, and meaningful for students. Therefore, strengthening lecturers’ efficacy needs to be an important part of efforts to improve the quality of learning at Islamic higher education institutions. ABSTRAKEfikasi dosen merupakan salah satu faktor penting yang memengaruhi kualitas pembelajaran di perguruan tinggi, khususnya pada Program Studi Pendidikan Agama Islam (PAI) yang menuntut integrasi antara kompetensi akademik, pedagogik, dan nilai-nilai keislaman. Penelitian ini bertujuan untuk menganalisis efikasi dosen dalam meningkatkan kualitas pembelajaran pada Program Studi Pendidikan Agama Islam Universitas Islam KH. Ruhiat Cipasung Tasikmalaya. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui wawancara mendalam, observasi, dan studi dokumentasi terhadap 5 dosen tetap, 1 Ketua Program Studi, dan 10 mahasiswa. Analisis data dilakukan menggunakan model interaktif Miles, Huberman, dan Saldaña yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa dosen memiliki tingkat efikasi yang tinggi dalam penguasaan materi, penerapan strategi pembelajaran, pengelolaan kelas, pelaksanaan evaluasi, dan pemanfaatan media pembelajaran. Efikasi dosen didukung oleh pengalaman mengajar serta dukungan institusional melalui pelatihan dan supervisi akademik. Temuan penelitian menunjukkan bahwa efikasi dosen berkontribusi terhadap terciptanya pembelajaran yang lebih efektif, partisipatif, dan bermakna bagi mahasiswa. Oleh karena itu, penguatan efikasi dosen perlu menjadi bagian penting dalam upaya peningkatan mutu pembelajaran di perguruan tinggi Islam.